Single Session Low Frequency Left Dorsolateral Prefrontal Transcranial Magnetic Stimulation Changes Neurometabolite Relationships in Healthy Humans - Bridges, Nathaniel R.; McKinley, Richard A.; Boeke, Danielle; Sherwood, Matthew S.; Parker, Jason G.; McIntire, Lindsey K.; Nelson, Justin M.; Fletchall, Catherine; Alexander, Natasha; McConnell, Amanda; Goodyear, Chuck; Nelson, Jeremy T. (Frontiers in Human Neuroscience, 2018)
Background: Dorsolateral prefrontal cortex (DLPFC) low frequency repetitive transcranial magnetic stimulation (LF-rTMS) has shown promise as a treatment and investigative tool in the medical and research communities. Researchers have made significant progress elucidating DLPFC LF-rTMS effects—primarily in individuals with psychiatric disorders. However, more efforts investigating underlying molecular changes and establishing links to functional and behavioral outcomes in healthy humans are needed. Objective: We aimed to quantify neuromolecular changes and relate these to functional changes following a single session of DLPFC LF-rTMS in healthy participants. Methods: 11 participants received sham-controlled neuronavigated 1Hz rTMS to the region most activated by a 7-letter Sternberg task (SWMT) within the left DLPFC. We quantified SWMT performance, functional magnetic resonance activation and proton magnetic resonance spectroscopy neurometabolite measure changes before and after stimulation. Results: A single LF-rTMS session was not sufficient to change DLPFC neurometabolite levels and these changes did not correlate with DLPFC activation changes. Real rTMS, however, significantly altered neurometabolite correlations (compared to sham rTMS), both with baseline levels and between the metabolites themselves. Additionally, real rTMS was associated with diminished reaction time performance improvements and increased activation within the motor, somatosensory and lateral occipital cortices. Conclusion: These results show that a single session of LF-rTMS is sufficient to influence metabolite relationships and causes widespread activation in healthy humans. Investigating correlational relationships may provide insight into mechanisms underlying LF-rTMS.